Cardiac Tumor Pathology - Basso, Cristina; Valente, Marialuisa; Thiene, Gaetano; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana Press, 2013)
Cardiac tumors were once a nosographic entity of scarce clinical interest because of the rarity and of the intrinsic diagnostic and therapeutic impossibilities, and were considered a fatal morbid entity. It has now become a topical subject due to advances in clinical imaging (echo, magnetic resonance, computed tomography) as well as innovation in technologies of in-vivo diagnosis. Cardiac Tumor Pathology presents a spectacular example of these advances with clinico-pathologic correlations. This timely volume covers history, epidemiology, demographics, clinical diagnosis, pathology, imaging by echo, CT and MRI of both benign and malignant cardiac tumors, either primary or secondary. Chemotherapy of malignant neoplasms is also addressed. Special emphasis is given to clinico-pathologic correlations. With all chapters written by experts in their fields, this volume will serve as a useful resource for physicians dealing with, and interested in, this special branch of cardiac oncology and will represent a useful guide for pathologists, clinicians, cardiologists, cardiac surgeons, and radiologists as well as for postgraduate students training in these areas.
Introduction: Cardiac tumors in the era of cardiovascular surgery and imaging -- Cardiac tumors: classification and epidemiology -- Cardiac myxoma -- Other benign cardiac tumors -- Cardiac tumors in the paediatric age -- Primary malignant cardiac tumors -- Cardiac metastases -- Echocardiographic diagnosis -- New cardiac imaging techniques: magnetic resonance and computed tomography -- Cardiac surgery -- Chemotherapy and cardiotoxicity.
Keywords: Medicine; Radiology, Medical; Cardiology; Oncology; Pathology; Medicine & Public Health; Pathology; Oncology; Cardiology; Diagnostic Radiology